Design Process: interaction methodology between design and engineering as an innovation vector - Barcellos, Ekaterina Emmanuil Inglesis; Botura Junior, Galdenoro (Gestão & Tecnologia de Projetos (Design Management and Technology), 2019)
Design and technology are innovative and creative and processes which use engineering to get the necessary technical support for the development of a universe of products, services and benefi ts for the consumption society. In order to leverage innovation, bringing together design and engineering provess to be an appropriate disciplinary creative strategy to facilitate this process. The search for optimization, innovation, benchmarking and better results for the users and their needs should resort to the application of the methodology of the “Design Process”. The technical and creative Design Process has its roots coming from the engineering concepts that are also inherent to design. Involves tailoring the usual methods of design and development for both areas, where also the project in stages works, the conception phase to the fi nal product. There are design processes and normal development in both areas, which also project in stages, involving organizational ergonomics concepts from conception to the fi nal product. This study o( ers a brief analysis of the methodological process of “Design Process”, to elucidate the tangent points in both methods of Design and Engineering, demonstrating that the approach between these areas improves the performance of products and services. By identifying this common approach, this study demonstrated that this partnership optimizes results with the potential for improvement on generating of innovation.